Labor market segmentation using Stochastic Markov chains (2009)
This article discusses regional labor segmentation using stochastic Markov chains. We present a formal model and derive preliminary results using the evolution of wages in Colombian urban areas. The results show that there was regional labor market segmentation in wages for university graduates during the period from 1993 to 2000, and corroborate the existence of structural changes in wages during the nineteen nineties.